Analisis Komplikasi Mikrovaskuler: Perbedaan Neuropati pada Pasien Diabetes Melitus yang Berobat Teratur dengan yang Tidak Teratur - Taufiqur Rahman; Prastomo Suhendro; Nindawi Nindawi; Mufidah Mufidah (Malahayati Nursing Journal, 2025)
ABSTRACT Neuropathy is a nerve disorder due to chronic complications of Diabetes, characterized by tingling, pain or numbness. Diabetic neuropathy more often attacks the nerves in the feet. Diabetes Mellitus is a metabolic disorder characterized by chronic hyperglycemia that occurs due to disorders in insulin secretion and insulin action. The incidence of diabetes mellitus in Indonesia is 1785 cases that experience complications divided into: 16% of diabetes mellitus patients experience macrovascular complications, 27.6% experience microvascular complications such as diabetic neuropathy. Factors that can prevent and inhibit the progression of neuropathy are patient compliance in taking medication. Diabetes mellitus patients are often not disciplined in carrying out a healthy lifestyle such as consuming a balanced nutritional intake, physical activity and also in taking medication. The results of this study are used as study material for nurses for an education model with data-based planning (PBD) that utilizes data to improve the quality of the counseling matrix. This study aims to determine the difference in the level of neuropathy in diabetes mellitus patients who receive irregular treatment and those who receive regular treatment at the Mohammad Noer Pamekasan Hospital. The type of research is descriptive comparative. The research subjects were 20 people selected using purposive sampling technique. The research data were taken from filling out the questionnaire, and analyzed using the Mann Whitney test statistic. The results of this study indicate that there is a significant difference in the level of neuropathy in diabetes mellitus patients who receive regular treatment and those who do not receive regular treatment at RS. Mohammad Noer Pamekasan (p value = 0.002 0.05). The conclusion of the results of this study indicates that there is a difference in the level of neuropathy that is more severe in diabetes mellitus patients who receive irregular treatment compared to those who receive regular treatment, therefore innovative education with a nursing management perspective approach is an important pillar in improving the ability to manage self-care for DM patients. Keywords: Diabetes Mellitus, Neuropathy, Irregular Medication  ABSTRAK Neuropati merupakan gangguan saraf akibat komplikasi kronis penyakit Diabetes, yang ditandai dengan kesemutan, nyeri atau mati rasa. Neuropati diabetik lebih sering menyerang saraf di kaki. Diabetes Melitus merupakan kelainan metabolik dengan karakteristik hiperglikemia kronik yang terjadi akibat adanya gangguan pada sekresi insulin dan kerja insulin. Angka kejadian diabetes melitus di Indonesia sebanyak 1785 kasus yang mengalami komplikasi terbagi dari: 16% penderita diabetes melitus mengalami komplikasi makrovaskuler, 27,6% mengalami komplikasi mikrovaskuler seperti neuropati diabetik. Faktor yang dapat mencegah dan menghambat progesivitas neuropati adalah kepatuhan pasien dalam minum obat. Penderita diabetes melitus seringkali tidak disiplin dalam melakukan pola hidup sehat seperti mengkonsumsi asupan gizi yang seimbang, aktivitas fisik dan juga dalam mengkonsumsi obat.  Hasil penelitian ini sebagai bahan kajian bagi perawat untuk model edukasi dengan perencanaan berbasis data (PBD) yang memanfaatkan data untuk meningkatkan kualitas matrik penyuluhan. Penelitian ini bertujuan untuk mengetahui adanya perbedaan tingkat neuropati pada pasien diabetes melitus yang berobat tidak teratur dengan yang berobat teratur di RS. Mohammad Noer Pamekasan.  Jenis penelitian adalah deskriptif komparatif. Subjek penelitian berjumlah 20 orang yang di pilih menggunakan teknik purposive sampling. Data penelitian diambil dari pengisian kuesioner, dan dianalisis menggunakan statistik uji Mann whitney.  Hasil penelitian ini menunjukkan terdapat perbedaan yang signifikan tingkat neuropati pada pasien diabetes melitus yang berobat teratur dengan yang tidak teratur di RS. Mohammad Noer Pamekasan (p value = 0,0020,05). Kesimpulan hasil penelitian ini menunjukkan bahwa adanya perbedaan tingkat neuropati yang lebih berat pada pasien diabetes melitus yang berobat tidak teratur dibandingkan dengan yang teratur, oleh karena itu edukasi yang inovatif dengan pendekatan perspektif manajemen keperawatan merupakan pilar penting dalam meningkatkan kemampuan mengelola perawatan diri/self care bagi penderita DM. Kata kunci: Diabetes Melitus, Neuropati, Berobat Tidak Teratur